Informational segmentation in international capital markets - Jack E. Wahl (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1988)
The economic influence of barriers to international information acquisition and, hence, of informational segmentation in international capital markets depends heavily upon the prevailing level of risk aversion. We find that these barriers are likely to have second order economic impact only. Furthermore, improving international informational integration is likely to Increase all asset prices when causing less heterogeneity of international subjective probability beliefs.
Keywords: 330